TEMPERATURE-DEPENDENT RELATIONSHIP BETWEEN INDIRECT TENSILE STRENGTH AND STIFFNESS MODULUS OF SBS-MODIFIED ASPHALT MIXTURES - Suparma, Latif Budi; Rahman, Taqia (Journal of Applied Engineering Science, 2026)
This study investigated the temperature-dependent relationship between indirect tensile strength (ITS) and indirect tensile stiffness modulus (ITSM) in styrene–butadiene–styrene (SBS) polymer-modified asphalt mixtures using a PG 76-22 binder. Cylindrical specimens were tested at four temperatures (20, 30, 40, and 50°C) to evaluate their tensile resistance and stiffness. The results show that both ITS and ITSM decrease markedly with increasing temperature, reflecting a reduction in binder viscosity and a weakening of aggregate interlock. Statistical analysis confirmed a strong positive correlation (r = 0.914, p < 0.001) between ITS and ITSM, with linear regression (R² = 0.9045) indicating that ITS is a reliable predictor of ITSM. An analysis of variance showed that temperature had significant effects on ITS and ITSM. These findings highlight the coupled mechanical behavior of ITS and ITSM, supporting their integration into mechanistic-empirical pavement design and performance-based mix evaluation. The study reinforces the role of SBS modification in enhancing thermal resilience and provides a practical framework for predicting stiffness modulus from tensile strength under varying thermal conditions.
Keywords: SBS-modified asphalt, indirect tensile strength, stiffness modulus, temperature sensitivity, regression modelling